Pembelajaran Pendidikan Pancasila dan Kewarganegaraan Sekolah Menengah Atas Negeri Kota Surakarta Tahun 2005/2006 - -, Sutoyo (Exsplorasi, 2006)
ABSTRACTLearning Pancasila and Civics Education of SMA Negeri Kota Surakarta in 2005/2006. This study aims to completely analyzs on learning PPKn (Pancasila and Civis Education) at SMA Negeri Kota Surakarta it used the internal-purfosive sampling technique. The data included informants location, and event at school environment as well as document. Data gathering were though interviews, observation, and document noting. The technique of triangulatuon data was used to determine the data validity, and interactive model was used for analyzing data.The result of this study indicates that :(1) learning PPKn at SMA Negeri Kota Surakarta for class X and XI has employed innovative learning.whereas class III, in general, uses conventional method ; (2) learning media of PPKn at SMA Negeri Kota Surakarta is largely insufficient; (3) in general, the exsitence of the teachers of SMA Negeri Kota Surakarta has been relevant to he level of education (S1 graduation) ; (4) most of the students of SMA Negeri Kota Surakarta concerns the subject of PPKn.Key words : learning Pancasila and civics education